Efficacy of nutrition therapy for glucose intolerance in Japanese women diagnosed with gestational diabetes based on IADPSG criteria during early gestation. Issue 3 (March 2015) - Horie, Ichiro; Kawasaki, Eiji; Sakanaka, Ai; Takashima, Miwa; Maeyama, Miwa; Ando, Takao; Hanada, Hirokazu; Kawakami, Atsushi
Abstract Aims Among women with gestational diabetes mellitus (GDM), the aggravation of glucose intolerance during gestation differs substantially. We retrospectively investigated whether the glucose intolerance of women diagnosed with GDM during early gestation (i.e., early-onset GDM) improved in the mid-gestation under appropriate nutrition therapy. Methods We conducted a longitudinal analysis of glucose tolerance derived from 75-g oral glucose tolerance test (OGTT) in 41 Japanese women with early-onset GDM defined by International Association of Diabetes and Pregnancy Study Group criteria during early gestation (<20 weeks). Glucose tolerance was also evaluated in mid-gestation (24–32 weeks) and postpartum. Insulin sensitivity, insulin secretion, and β-cell function were assessed at each period. Results The glucose tolerance in 18 of the 41 early-onset GDM patients normalized during mid-gestation with appropriate nutrition therapy, defined as GDM → NGT. These women did not require insulin therapy during their pregnancies, whereas 39.1% of women who retained GDM in mid-gestation (defined as GDM → GDM) required insulin therapy. The frequency of the postpartum development of type 2 diabetes or impaired glucose tolerance was significantly lower (5.6% vs. 39.1% in GDM → NGT vs. GDM → GDM, p = 0.03). Primiparity was determined as a predictive factor whether or not glucose intolerance was improved by nutrition therapy, but results of plasma glucose levels from OGTT at early gestation were not, in a multivariate logistic regression analysis. Conclusions Appropriate nutrition therapy for women with early-onset GDM seemed effective to improve glucose tolerance during pregnancy. OGTT retesting during their mid-gestation seemed effective for predicting the appropriate treatment after the second trimester.